PERSONAL BRANDING STRATEGI UNTUK MEMENANGKAN PASAR - Diana Novita; Aerwanto, Aerwanto; Muhamad Hadi Arfian; Hanifah, Hanifah; Susanto, Susanto; Sri Purwati; Hedar Rusmana (Journal of Innovation Research and Knowledge, 2024)
Personal branding has emerged as a crucial strategy in contemporary professional contexts, influencing individuals across various industries and career stages. This study explores the concept of personal branding, focusing on its definitions, theoretical foundations, and practical implications. Through a comprehensive review of existing literature, the research identifies key elements and strategies that individuals employ to cultivate and manage their personal brands effectively. Moreover, it examines the impact of personal branding on career development, reputation management, and professional success. The findings highlight the importance of authenticity, consistency, and strategic communication in building a strong personal brand. The study contributes to existing knowledge by providing insights into how individuals can leverage personal branding to enhance their visibility, credibility, and influence in competitive environments. Future research directions are proposed to further explore the evolving nature of personal branding in the digital age